STRATEGI SOSIALISASI IZIN MENDIRIKAN BANGUNAN DI DESA BILA KECAMATAN DUA PITUE KABUPATEN SIDENRENG RAPPANG - Syafaruddin Syafaruddin; Mirnawati Mirnawati; Sapri Sapri; Muhammad Arisal Asad (JIA: Jurnal Ilmiah Administrasi, 2020)
strategy of socializing the establishment of buldings in the Bila village, Dua Pitue district of sidenreng rappang regency. This study aims to determine the strategy of socializing building permits that from building in the Bila village, Dua Pitue district of Sidenreng Rappang regency and to find out the factors that influence the socialization strategy to build a building license iin the Bila village Dua Ptitue district of Sidenreng Rappang Regency. The population of this study was the village community if as many as 3.028 people by taking a sample of 97 people withdrawal technique used is purpossive sampling. This typpe of rescearch is descriptive quantitative. The data collcection technique used is observation, interview, questionnaire and literature study. Thee technique of the data abalysis used is descriptive statistics and with the help of the SPSS version 16 application. The result showed that the socialization strategy for establishing building licenses in Bila village viewed from three indicators of the socialization process : preparation, ready to act and the acceptance of collective norms obtained a result of 58 % of the expected result of 100 %. This shows that the socialization strategy of establishing building permits in the Bila village in the category is not good and still needs to be reviewed. Factors that influence the socialization strategy of establishing building permits in Bila village viewed from external factors : education, environment, employment adn internal factors : motivation, interest, aability to get 57 % of the expected result 100 %. This shows that the factors that affect the socialization strategy of establishing building permits are in the poor category.